The Uneven Effect of Financial Constraints: Size, Public Ownership, and Firm Investment in Ethiopia. (September 2017) - Lashitew, Addisu A.
Highlights: The study investigates if investment among small and private firms is disproportionately affected by financial constraints in Ethiopia. Analysis is based on impulse responses derived from a panel VAR model. Investment among small firms is sensitive to financial factors, indicating financial constraints. The analysis that compares private and public firms is less conclusive. The results indicate that financial constraints that affect the growth of small firms could undermine industrial performance in Africa. Summary: This study investigates if financial constraints reduce investment among private and small firms using a rich, census-based dataset of manufacturing plants from Ethiopia. Impulse responses from a panel VAR estimation are used to compare the response of investment to changes in cash flow and the marginal product of capital among plants with different size and ownership status. The analysis reveals that cash flow has greater effect on investment among small plants, whereas the effect of the marginal product of capital is greater among large plants. This indicates that small plants are more financially constrained than large plants even though they have significantly higher marginal product of capital. Comparison between public and private firms is less conclusive, showing that size rather than ownership is strongly associated with financial constraints in Ethiopia. The results indicate that financial market imperfections could undermine industrial performance in Africa by limiting the growth of small firms.